A National Quality Assurance program for breast immunohistochemistry: an Italian perspective - GUADAGNO, E.; DE ROSA, G.; NAPPI, O. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
A national project for the quality assessment of breast immunohistochemistry,involving 155 pathology laboratories distributed all over the Italian territory ( 19 regions), was carried out. The Project lasted one year from December 2014 to December 2015 and it was strongly supported by the Italian Society of Anatomic Pathology (SIAPEC/IAP). Proficiency tests were carried out by the Nordic Immunohistochemical Quality Control (NordiQC) organization. The main aim of the project was to investigate on the general performance of immunohistochemistry (ER, PR and HER2) in the field of breast cancer in the Italian territory, in order to emphasize any difference and give practical support to laboratories in daily practice.The present review article focused on the description of this extraordinary pioneer Italian experience. Besides NordiQC results, further analysis concerning epidemiology and geographical distribution were done.Aim of the study was to analyze the general results and to discuss on the benefits that a national quality control program may have if it became a mandatory service provided by the National HealthCare System.In general, the Italian data were in accordance with the general results obtained from the “official” NordiQC HER2, PR and ER assessments. A HER2 scoring consensus between labs and assessorgroup was achieved in 80% of cases.Interestingly, what emerges from our study is that no substantial differences exist among the three Italian macro-areas (North, Center and South) in the quality of Immunohistochemistry performed for breast cancer. No statistically significant difference was even found between laboratories that perform more or less than 100 tests/year.